Peranan Fisioterapi pada Kasus Hallux Valgus (Bunion) dengan Intervensi NMT dan Strengthening untuk Mengurangi Nyeri - Ismaningsih Ismaningsih; Nova Relida Samosir; Maulidya Maulidya (Jurnal Ilmiah Fisioterapi, 2021)
Background Hallux valgus (HV), also known as bunion is one of the most common foot deformities. It manifests with the proximal phalanx deviating laterally and the first metatarsal head deviating medially, usually due to adduction of the first metatarsus, called the metatarsus primus varus. The deformity is sometimes red in color and very painful to daily activities. If identified and treated properly the symptoms will improve. The exact etiology is not fully understood. It tends to occur more frequently in women and those who wear shoes or tight heels, hallux valgus is found in 58% of women and 25% of men. HV deformities can usually be diagnosed by physical examination. This deformity is sometimes red in color and painfully interferes with daily activities. If identified and treated properly the symptoms will improve. The aim of this study was to determine the effect of neuromuscular taping intervention and strengthening exercise on pain reduction. The Research Method is a literature study consisting of sources -the research source used the final evaluation, namely the Visual Analogue Scale (VAS). The results in the literature study showed a reduction in pain after neuromuscular taping and strengthening exercises. From this literature study it can be concluded that the intervention of neuromuscular taping and strengthening exercise is effective in reducing pain. , increases the strength of M. Abductor hallucis muscles as well as reduces the hallux valgus angle.